Transitional Challenges And Factors Affecting English-Speaking Learners In Learning The Filipino Language (Journal of Namibian Studies : History Politics Culture, 2023)
Learning a new language can present numerous difficulties, especially for individuals who are native English speakers and are embarking on the journey of acquiring the Filipino language. This study aimed to determine the transitional challenges faced by English-speaking learners during the process of acquiring proficiency in Filipino, as well as identify the factors that affect their language-learning journey. By understanding these challenges and factors, educators and language instructors can design effective strategies and interventions to facilitate a smoother transition for English-speaking learners into learning the Filipino language. This study used qualitative design as a research method, data were collected from 8 participants through interviews. Exploratory research was carried out to extract narratives and experiences that are relevant to English-speaking learners in learning the Filipino language. The results showed that English-speaking learners often struggle with understanding and speaking the language, particularly with pronunciation, grammar structures, and vocabulary. Additionally, learners may lose interest in the language, making language acquisition more difficult. The factors that facilitate the language transition process were interest and exposure to the target language. The findings of this research will contribute to the existing literature on second language acquisition, specifically focusing on the challenges and factors affecting English-speaking learners in learning the Filipino language. The results will provide valuable insights for language educators and curriculum developers to develop effective teaching methodologies, language materials, and support systems to facilitate a more successful transition for English-speaking learners.